1993
DOI: 10.1080/00380768.1993.10416992
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic nitrification in acid tea soils

Abstract: Investigations to analyze the nature of nitrification in acid soils were carried out in the laboratory using 2 soil types from a tea field. The optimum temperature for the nitrification activity in these soils was 25~ and the activity was inhibited above 35"C, suggesting that the nitrifying bacteria became adapted to the soil conditions. The optimum NH4+-N concentrations for nitrification ranged between 20 and 200 mg N/100 g of soil and the activity decreased at a concentration above 300 mg N. The effect of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
27
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(30 citation statements)
references
References 29 publications
3
27
0
Order By: Relevance
“…This similarity strongly supports our hypothesis that pH, within wide limits, does not primarily control growth and activity of nitrifiers. Our findings are in line with the observation that the increased addition of calcium carbonate to acidic tea soils does not affect nitrification rate (30).…”
supporting
confidence: 82%
“…This similarity strongly supports our hypothesis that pH, within wide limits, does not primarily control growth and activity of nitrifiers. Our findings are in line with the observation that the increased addition of calcium carbonate to acidic tea soils does not affect nitrification rate (30).…”
supporting
confidence: 82%
“…Though the pH of the surface tea soils used ranged from 3.2 to 3.8, the concentration of N0 3 --N in soils was high ( Table 1). This finding is in agreement with the report that nitrification can occur in tea soils despite the low pH of about 3.5 (Hayatsu and Kosuge 1993). Hayatsu (1993) was able to isolate acidophilic NH4 + oxidizers from tea soils.…”
Section: Bacteriasupporting
confidence: 83%
“…Hayatsu (1993) was able to isolate acidophilic NH4 + oxidizers from tea soils. Hayatsu and Kosuge (1993) reported that nitrification was completely inhibited in the tea soils treated with nitrapyrin or acetylene, suggesting that nitrification in the strongly acid tea soils was caused by autotrophic NH4 + -oxidizing bacteria. However, lower numbers of autotrophic NH4 + oxidizers than autotrophic NO z -oxidizers especially in the Kuroniga, Taisekigan, and Anzangan soils were observed (Fig.…”
Section: Bacteriamentioning
confidence: 99%
“…Pommerening-Roser et al recently described six lineages in the genus Nitrosomonas based on 165 rRNA sequence and DNA-DNA hybridization analyses, and showed that the existence of lineages of the species in the genus Nitrosomonas was consistent with ecophysiological distinctions among the species (Pommerening-Roser et al, 1996). Further delineation of the phylogenetic relationships among beta-subdivision ammonia oxidizers will continue for additional isolates obtained from diverse environments (deBoer and Laanbroek, 1989;Hayatsu and Kosuge, 1993;Jones et al, 1988;Koops et al, 1991;Stehr et al, 1995;Suwa et al, 1994;Utaker et al, 1995).…”
mentioning
confidence: 99%